A strength-based mirror effect persists even when criterion shifts are unlikely. - Koop, Gregory J.; Criss, Amy H.; Pardini, Angelina M. (Memory & Cognition, 2019)
In single-item recognition, the strength-based mirror effect (SBME) is reliably obtained when encoding strength is manipulated between lists or participants. Debate surrounds the degree to which this effect is due to differentiation (e.g., Criss Journal of Memory and Language, 55, 461–478, 2006) or criterion shifts (e.g., Hicks & Starns Memory & Cognition, 42, 742–754, 2014). Problematically, differing underlying control processes may be equally capable of producing an SBME. The ability of criterion shifts to produce an SBME has been shown in prior work where differentiation was unlikely. The present work likewise produces an SBME under conditions where criterion shifts are unlikely. Specifically, we demonstrate that an SBME can be elicited without the typical number of trials needed to adjust one's decision criterion (Experiments 1, 2, and 5) and using encoding manipulations that do not explicitly alert participants that their memory quality has changed (Experiments 3 and 4). When taken in the context of the broader literature, these results demonstrate the need to prioritize memory models that can predict SBMEs via multiple underlying processes.